2018
DOI: 10.4103/ejd.ejd_49_18
|View full text |Cite
|
Sign up to set email alerts
|

The anti-inflammatory effect of the platelet-rich plasma in the periodontal pocket

Abstract: Objective:Chronic periodontitis (CP) is a common inflammatory disease that causes destruction to the supporting tissues of the teeth. Many treatment modalities tried to stop the disease progression. Platelet-rich plasma (PRP) is one of the regenerative methods that used in adjunct to conventional periodontal treatment. The aim of this study was to evaluate the anti-inflammatory effect of PRP by monitoring the lymphocyte count before and after its application to the periodontal pocket.Materials and Methods:Twen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 14 publications
1
26
0
Order By: Relevance
“…However, when macrophages were challenged with pro-or anti-inflammatory factors (M1 and M2 medium, respectively), the secretion of both pro-(MIP1α and TNFα) and anti-inflammatory (IL1-ra) cytokines were modulated; PRPr dampened the production of MIP1α and the content released from our composite scaffolds allowed macrophages to secrete both MIP1α and TNFα to the same levels as 10% FBS, while increasing the level of IL1ra secretion. Indeed, anti-inflammatory effects of PRP have previously been reported in different applications (Zhang et al, 2013;Moussa et al, 2017;Abdul Ameer et al, 2018); although other groups reported stimulation of both M1 and M2 markers (Escobar et al, 2018). The study of macrophage polarization is an evolving field, with several cytokines and markers expressed by subpopulations that may go beyond the classical M1/M2 and pro-/anti-inflammatory phenotypes (Chávez-Galán et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, when macrophages were challenged with pro-or anti-inflammatory factors (M1 and M2 medium, respectively), the secretion of both pro-(MIP1α and TNFα) and anti-inflammatory (IL1-ra) cytokines were modulated; PRPr dampened the production of MIP1α and the content released from our composite scaffolds allowed macrophages to secrete both MIP1α and TNFα to the same levels as 10% FBS, while increasing the level of IL1ra secretion. Indeed, anti-inflammatory effects of PRP have previously been reported in different applications (Zhang et al, 2013;Moussa et al, 2017;Abdul Ameer et al, 2018); although other groups reported stimulation of both M1 and M2 markers (Escobar et al, 2018). The study of macrophage polarization is an evolving field, with several cytokines and markers expressed by subpopulations that may go beyond the classical M1/M2 and pro-/anti-inflammatory phenotypes (Chávez-Galán et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These outcomes implied that PDB could retard the bone loss and improve bone recovery. The effectiveness of PDB could also be ascribed to the anti-inflammatory activities of TGF-β1 [ 35 ] and lipoxins [ 36 ], modulating repair of inflamed tissues leading to bony matrix restoration [ 37 ] and regeneration [ 38 ]. Furthermore, the other PDB-contained growth factors in the cocktail which may participate in therapeutic outcomes include platelet-derived growth factor (PDGF) epidermal growth factor (EGF), hepatocyte growth factor (HGF) and basic fibroblast growth factor (bFGF) [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, the huge loss of chondrocytes and PG in wavy fibrils of collagen fibers of extracellular matrix, as revealed by H&E, IHC, and alcian blue staining in nicotine-induced OA group, accounts for cartilage destruction score of over 3, which was decreased to 50% after PDB intervention. These therapeutic efficacies of PDB might also be attributed to the anti-inflammatory activities of TGF-β1 32 and lipoxins 33 , regulating repair of inflamed tissues leading to matrix restoration 34 and regeneration 35 . Further, the therapeutic efficacies of PDB may also be attributed to growth factors such as hepatocyte growth factor (HGF), epidermal growth factor (EGF), and fibroblast growth factor, which are present as a cocktail.…”
Section: Discussionmentioning
confidence: 99%